The Americanization of Confucian Filial Piety in Disney’s Mulan (1998) - Christina Christina; Setefanus Suprajitno (Institute of Research and Community Outreach - Petra Christian University, 2014)
This study is concerned with the Americanized exposure of Confucian filial piety expressed in one of Disney’s animated features, Mulan. I intend to analyze how Disney reframes the original concept of Confucian filial piety to meet the global understanding of Disney’s audience and how Disney’s fundamental motives affect Disney’s decision on combining Confucian filial piety with American values. In the analysis, I use three main theories, namely americanization, disneyfication, and cultural hybridity related to cultural imperialism. In my analysis, I find that Disney reframes the original concept of Confucian filialness in a more Americanized manner, by injecting some classic American notions such as individualism and equality of opportunity in order to preserve Disney’s standardized formula. And yet, the most significant motive is Disney’s marketing purpose related to the acceptance of Disney’s audience and Disney’s reputation as a showbiz industry.